Effects of harvest time and storage on dietary fibre components in various cultivars of white cabbage (Brassica oleracea var capitata) - Wennberg, Mathias; Engqvist, G; Nyman, Margareta (Journal of the Science of Food and Agriculture, 2002)
The effect of harvest time and storage on dietary fibre content and composition was investigated in six cultivars of white cabbage (Brassica oleracea var capitata). Three cultivars were of early maturity type (SW Nordpol, Rolly and Balbro) and three of late maturity type (Predikant, Hanna and Lion). The average total dietary fibre (TDF) content was 241 g kg(-1) dry matter (DM) (CV = 13), of which approximately 25% was soluble (CV = 15). The main dietary fibre components were glucose (37%), uronic acid (32%), arabinose (12%) and galactose (8%) residues. Early cultivars generally had a lower TDF content than late maturity types, due to a lower amount of both insoluble (arabinose, galactose and glucose) and soluble (arabinose) polymers. An early cultivar, Rolly, had the highest solubility, 33%, versus 25 +/- 4% for the other cultivars. The early cultivar SW Nordpol had a similar TDF content and proportion of soluble dietary fibre (SDF) to the late cultivar Hanna, but the dietary fibre composition was different, with the early cultivar having a lower proportion of arabinose residues. Storage for 6 weeks had minor effects on the dietary fibre. After further storage of the late maturity cultivars, there was an increase in insoluble dietary fibre (IDF) (glucose and uronic acid residues) and a decrease in SDF (arabinose and galactose residues). As a consequence the solubility of TDF decreased from 29 to 19% on average. Harvesting before physiological maturity was reached resulted in a somewhat lower content of TDF and 11317 for two cultivars (Predikant and Hanna), while SDF was more or less unaffected for all cultivars. Long-term storage had fewer effects on cabbage harvested prior to maturity than when harvested at the right physiological maturity. It is concluded that the observed differences between cultivars and after long term storage are of such magnitude that they may affect nutritional properties of the dietary fibre.